2005
DOI: 10.1303/aez.2005.563
|View full text |Cite
|
Sign up to set email alerts
|

Effects of aerial insecticide sprays on ant communities to control pine wilt disease in Korean pine forests

Abstract: Pine wilt disease is one of the most serious diseases in the pine forests of Korea. Since the first report of the disease in Busan, Korea, in 1988, the disease has been gradually spreading into neighboring regions and now occurs in many regions of the southern part of the Korean Peninsula. The control of the disease is focused on the killing of the sawyer, Monochamus alternatus, an insect vector, by aerial insecticide spraying for adult control and by fumigation or burning infected trees for larval control. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 21 publications
0
20
0
Order By: Relevance
“…For example, Kwon et al (2005) found that N. flavipes was by far the most common ant collected in Korean forests. In areas of the U.S. where it invades, N. flavipes seems to blend inconspicuously into the community like a native species (S. Cover, personal communication).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Kwon et al (2005) found that N. flavipes was by far the most common ant collected in Korean forests. In areas of the U.S. where it invades, N. flavipes seems to blend inconspicuously into the community like a native species (S. Cover, personal communication).…”
Section: Discussionmentioning
confidence: 99%
“…According to their main foraging habitat, Kwon et al (2012) devised five Korean ant functional guilds as follows: forest ground forager (FGF), forest vegetation and ground forager (FVGF), forest vegetation forager (FVF), soil and litter forager, and grassland forager. This guild system has been devised from previous field studies in seven metropolitan cities which included forest sites and open-land sites (T-SK, unpublished data), ant survey for 14 years in soils of eight forest sampling sites in four locations (T-SK, unpublished data), ant survey from ground to crown in pine forests (Kwon et al 2005), and nationwide ant survey . We unified FGF and FGVF as FGF, because these functional guilds cannot be clearly bifurcated, due to the lack of direct empirical evidence, and we changed the term of soil and litter forager to soil and litter dweller (SLD).…”
Section: Study Sitementioning
confidence: 99%
“…Ants respond quickly to forest disturbances of various types, e.g., livestock grazing (Nash et al 2004), tree cutting (Zettler et al 2004), fire (Andersen 1991), mining and farming (Majer 1983), and forest management (Maeto and Sato 2004;Arnan et al 2009). Hence, ants have been recognized as good bioindicators for the impacts of various disturbances such as mining, fire, pesticides, and logging (Andrew et al 2000;Maeto and Sato 2004;Kwon et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…In 2009, pine forests covering 15,000 ha were subjected to aerial spraying (Korea Forest Service, 2009), although the area of PWD infected forests in that year was estimated to be only 5633 ha (Korea Forest Service, unpublished). Information on aerial spraying is presented by Kwon et al (2005b) and Kwon (2008).…”
Section: Conventional Control (C) and Nematicide-injection (N)mentioning
confidence: 99%